Assessing ecological conditions for landscape management: a comparative analysis of field measurements and perceptions. (4th July 2022) - Mallette, Angela; Plummer, Ryan; Baird, Julia
Abstract: Assessments of ecosystem condition are fundamental to landscape management, and there are several sources of evidence practitioners may use. Perceptions of individuals is one of those sources, and understudied. This study quantitatively compares ecological field measurements and the perceptions of a group of key individuals. Findings reveal that perceptions did not statistically differ from the ecological assessment for elements of ecosystem composition (e.g. vegetation diversity and invasive species). However, differences were found for all other elements (e.g. ecosystem function, structure, and overall condition), such that the individuals tended to have lower ratings of ecosystem condition than ecological assessments. The findings highlight the importance of comparing different approaches for reciprocal verification of data and to identify opportunities to integrate evidence, thereby providing a more detailed picture of ecosystem condition.